'It Is Good to See the Person As a Whole Person and... Continue to Improve Our Psychologically Informed Working': A Thematic Analysis of Clinical Psychology Trainee Placements in Homelessness Settings. - Ward, Rebecca J.; Greenway, Frances T.; Maguire, Nick (Health Expectations, 2024)
Objectives: The National Framework for Inclusion Health identified the need for collaborative action between the NHS and third sector health to improve access and outcomes for Inclusion Health groups. Clinical psychology trainee placements in homelessness settings could be a valuable pathway to improving access to psychological support for people experiencing homelessness and the provision of clinical services, which is key to developing the workforce and a catalyst for the future recruitment of clinical psychologists in the third sector. Methods: A qualitative evaluation was conducted using semistructured interviews to explore the perspectives of clinical psychology trainees, supervisors, staff in homelessness settings and a peer mentor. Twenty‐two participants were recruited from two universities and six services across the South East, including 11 clinical psychology trainees, six supervisors, four placement staff and one peer mentor. Results: Placement staff described the value of a psychological approach but identified some challenges to be overcome. Induction was identified as the key to success. Supervisors recognised the breadth and depth added to trainees' knowledge and skills alongside significant challenges. Trainees valued the opportunities to work in homelessness settings and develop their understanding of the role. The peer mentor identified collaborative working as especially important. Conclusions: Clinical psychology trainee placements are a necessary programme to fulfil the NHS vision for Inclusion Health. These placements equip the health and social care workforce to create excellent and sustainable provisions to improve the physical and mental health of people experiencing homelessness whilst also providing much‐needed psychological support for staff. Patient and Public Contribution: Psychologically Informed Environments Through Staff Training: Staff training and support within these placements contribute to the development of psychologically informed environments. This not only leads to better outcomes for both staff and clients but also aligns with the objectives of the National Framework for Inclusion Health, fostering sustainable provision for the health needs of people experiencing homelessness (PEH).Enhanced Therapeutic Adaptability: Trainees gain invaluable experience in adapting therapy to meet the diverse needs of clients, benefiting both trainees and clients alike. This adaptability fosters more effective therapeutic relationships and contributes to the improvement of inclusion health provision in the long term.Tailored Therapy for Timely Intervention: Clinical psychology trainee placements in homelessness settings offer therapy that bypasses long waiting times for interventions, crucial for individuals experiencing homelessness. This flexible approach caters to the unpredictable engagement levels of PEH, ensuring timely support aligning with the Health and Care Act 2022 to improve overall health and address health disparities through primary care networks.